Faced with the latest attacks on the Health System. Economic cutbacks or model change? - Izco, Santiago (Razón y fe, 2018)
The cutbacks that our current Health System is suffering are, in the opinion of the author of this article, leading to substantial changes. So substantial that if the entire population does not react as a civil society, we will find ourselves with a system that is not only different from the previous one, but also unfair, unethical and in the hands of private companies with which we citizens had not signed up for. Principles such as equity and universality, basic in our Health System, have been thrown into the air since Royal Decree Law 16/2012 and the application of privatization policies in regions as influential as Madrid are being imposed.